Expression of Journalist Political Support through Social Media - Hidayati, Rita (KnE Social Sciences, 2019)
Social media as a new form of media opens up the individual’s display space in virtual life. Individual self-image is present in social media accounts so that it leads to a real identity. The expression of a journalist’s political support through social media has been considered part of his identity. The Alliance of Independent Journalists (AJI) as a professional organization has issued an appeal in the form of the Statement of Independent Journalist Alliance on Presidential Election, Social Media & Journalist and Media Independence. The statement of attitude was conveyed on August 18, 2018, by Abdul Manan as General Chair of AJI and the Revolution of Riza Secretary General of AJI, No. 049 / AJI / P.S / VIII / 2018, calling for three points of appeal. This research reveals the opinion of journalists in Central Java regarding the appeal. Although it has been regulated in Law 40 of 1999 concerning the Pers and Journalistic Code of Ethics (KEJ) rules bind the work of journalists, there are still many expressions of journalists in Central Java in conveying support to participants in the General Election. Using qualitative methods by collecting data through purposive sampling, the journalists responded to the AJI’s appeal with various reactions. They stated that social media is a part of self-image that a journalist must guard. There are journalists who agree with AJI’s appeal. But there are also those who disagree with the appeal on the grounds that freedom of opinion is, and he is not a member of AJI. So, he felt no need to obey the appeal. Keywords: Social Media, Journalist, Press, Media.